Development of Electronic Exhibition Audio Guide System Using VLC - Zaiton, AM.; Kamarul, AM.; Choon, ZG.; Ling, ZJ.; Shapiee, MSM.; Roslan, NS.; Teng, PC. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper reports a design and development of an indoor exhibition audio guide prototype using visible light communication. This project integrates high-speed communication network using light emitting diodes as a source and a transmitter to encode the information signal within an illumination framework. The received data is then decoded using Arduino microcontroller, which will decide the audio file to play through a headphone according to the displayed exhibits. This project successfully proposes a new technology that could be implemented and replaced the current technology used for electronic exhibitions audio guide.